2004
DOI: 10.1557/proc-830-d7.2
|View full text |Cite
|
Sign up to set email alerts
|

Organic Memory Devices Using C60 and Insulating Polymer

Abstract: In this paper, we describe an all organic molecular memory device that combines the advantages of molecular and organic electronics. We accomplish this by combining C 60 molecules with poly(4-vinylphenol) (PVP) and co-dissolving them in iso-propanol. The currentvoltage measurements show a large hysteresis in the blend devices, in contrast to pure PVP devices. The thin blend films have been thoroughly characterized using Raman spectroscopy, atomic force microscopy and scanning electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…First introduced by Kanwal et al (2005) at the Materials Research Society (MRS) conference in 2004, these devices also show the required characteristics for bistability and non-volatility. Subsequent devices studied by Majumdar et al (2005) showed that depending upon the concentration of C 60 , the devices exhibited either bistability or at higher concentrations WORM characteristics.…”
Section: Polymer Memory Devicesmentioning
confidence: 99%
“…First introduced by Kanwal et al (2005) at the Materials Research Society (MRS) conference in 2004, these devices also show the required characteristics for bistability and non-volatility. Subsequent devices studied by Majumdar et al (2005) showed that depending upon the concentration of C 60 , the devices exhibited either bistability or at higher concentrations WORM characteristics.…”
Section: Polymer Memory Devicesmentioning
confidence: 99%
“…Memory devices from organic materials have recently begun to receive attention. [2][3][4][5][6][7][8][9][10][11][12][13] Although there is a clear demand for next generation of nonvolatile solid state memories, the newcomer organic memory devices must exceed the existing speed and cost constraints of today's entrenched technologies. 3 In addition, the new technology must also meet other critical performance criteria such as long term data retention, low power consumption, and large number of rewrite cycles.…”
mentioning
confidence: 99%
“…105 ns. Here, it should be mentioned that both the response time and the equilibrium time of the current memory device are much faster than that (≈1 μs) of a NAND (NOT/AND) flash memory based on traditional semiconductors, and comparable to the current widely‐used dynamic random access memory (DRAM) and SRAM inorganic semiconducting memory devices (response time: <10 ns, access time: 60–100 ns or shorter) . The similar condition has occurred for 6F‐OCzTZ PI with a shorter equilibrium time of 85 ns.…”
Section: Resultsmentioning
confidence: 59%